Removal of Heavy Metals Ions from Aqueous Solution using Different Pretreatment Techniques of Corn Cob - Low, Wen Pei; Lee, Ee Yern; Chang, Fung-Lung; Nurharniza, Abdul Rahman (INTI International University, 2022)
Water pollution has been a global issue and Malaysian waters are of no exception. Traces of heavy metals have been found in rivers and water sources from industrial and agricultural run-off, apart from improper waste disposal. Hence, this study proposes the application of corn cob to remove Chromium (Cr), Manganese (Mn), and Lead (Pb) metal ions from aqueous solution by different pre-treatment techniques using vinegar and hydrochloric acid (HCl). The experiment was conducted in a water filtration apparatus where each heavy metal of interest were treated separately using the pre-treated corn cob. The samples of metal ions were tested by using Inductively Coupled Plasma-Atomic Emission Spectrometry (ICP-AES), which was later analysed and compared by evaluating the percentage removal of each metal ions, adsorption capacity, and adsorption isotherms. For Cr, Mn, and Pb removal using HCl-treated corn cob, the maximum percentage removal is 58.75%, 98.68%, and 77.18% respectively whilst the maximum percentage removal for Cr, Mn, and Pb using vinegar-treated corn cob is 71.50%, 98.00%, and 74.25%. Further analysis on the equilibrium data shows that this experiment favoured the Freundlich isotherm, as seen from the R2 values greater than 0.9 for each adsorption experiment. Hence, both corn cob pre-treated using HCl and vinegar was proven to be effective in the removal of Cr, Mn, and Pb ions.